The modeled CA 125 ELIMination rate constant K (KELIM) scores in predicting outcomes in advanced ovarian cancer undergoing neo-adjuvant chemotherapy and interval debulking surgery - Dawadi, Subodh Raj; Shrestha, Binuma; Acharya, Bijaya Chandra; Pandey, Manju; Gurung, Sarita Rana; Subedi, Hem Nath; Chaudhary, Jully; Oli, Asmita; Sharma, Dipti (Nepalese Journal of Cancer, 2026)
Objectives: To evaluate the prognostic utility of standardized KELIM score (derived from CA-125 kinetics) in predicting complete cytoreduction at interval debulking surgery (IDS) following neoadjuvant chemotherapy (NACT) in stage III-IV epithelial ovarian cancer patients at BPKMCH Chitwan. Methodology: Observational study of 46 eligible patients (from 58 total) treated January-December 2025 with carboplatin AUC6 + paclitaxel 175 mg/m² q3w (median 3 cycles). Standardized KELIM calculated using biomarkerkinetics. org calculator (≥1.0 favorable) from serial CA-125 measurements. RECIST 1.1 response assessment, surgical complexity, completeness of cytoreduction (CC0: no gross residual; CC1: <2.5 mm), and postoperative hospital stay was analyzed. Results: Mean age 59 years (range 29-78); 76% favorable KELIM (mean 1.28, median 1.31, range 0.47-2.22). CA-125 declined from 1498 IU/mL (pre-NACT) to 48 IU/mL (pre-IDS). RECIST: 26% complete response, 70% partial response, 4% stable disease. IDS achieved CC0 in 83% (38/46) and CC1 in 17%—superior to CHORUS (39%), EORTC (81%), SCORPION (77%) trials. Favorable KELIM predicted CC0 with 91% rate (OR 6.1, PPV 94%), simpler surgery (1.35 vs 1.09, p=0.059), and shorter stays (11.9 vs 13.9 days). Conclusion: KELIM ≥1.0 robustly predicts chemosensitivity and IDS success in advanced ovarian cancer. Favorable scores guide optimal patient selection while unfavorable KELIM identifies candidates for complex surgery, bevacizumab (ICON7/GOG-0218), or HIPEC (Cho et al.). NACT-IDS proves highly effective in highburden Nepali patients; larger prospective validation needed.